Drawpoint fragmentation analysis and application to flow modelling at Oyu Tolgoi - Batbayar, T (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
This paper reviews the fragmentation estimates and data collection on Oyu Tolgoi’s initial production area. The Hugo North Lift 1 area of the Oyu Tolgoi underground mine is a deep and highly altered orebody, initiating with P0. The size of the P0 cave is approximately 300 × 300 m and 1,300 m below surface. Waste overlies this initial area of roughly 800 m; therefore, fragmentation is critical to understand cave flow. Fragmentation data is collected using an automated photogrammetry tools and manual visual observations. Within this paper, the current analysis is presented which compares actual fragmentation observations with study estimates for P0 and how this data is incorporated in the flow models for the design of future block caving operations.
Keywords: Oyu Tolgoi; block cave; fragmentation; flow model